2017
DOI: 10.1097/hjh.0000000000001164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term exercise training on brain-derived neurotrophic factor signaling in spontaneously hypertensive rats

Abstract: Our results revealed that endothelial and neuronal BDNF expressions were both impaired in hypertension and that physical exercise improved hippocampal mBDNF levels and signaling through blood pressure-independent mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
4
11
0
Order By: Relevance
“…In agreement with this, BDNF +/− rats exhibited anhedonia and anxiety-like behaviour (15) and the Val66Met polymorphism that results in abnormal BDNF signalling (16) increased the risk of mental diseases (17,18). It is noteworthy that brain BDNF levels are decreased in diseases associated with ED (19,20) or after immune challenge (21).…”
Section: Introductionsupporting
confidence: 53%
“…In agreement with this, BDNF +/− rats exhibited anhedonia and anxiety-like behaviour (15) and the Val66Met polymorphism that results in abnormal BDNF signalling (16) increased the risk of mental diseases (17,18). It is noteworthy that brain BDNF levels are decreased in diseases associated with ED (19,20) or after immune challenge (21).…”
Section: Introductionsupporting
confidence: 53%
“…However, learning is impaired in animal model of RA in which only one hind paw is damaged (Zhu et al, 2016 ). It is noteworthy that diseases other than RA but combining as RA impaired cognition and high cardiovascular risk such as hypertension and diabetes were reported to induce BDNF downregulation in neurons (Pietranera et al, 2010 ; Franco-Robles et al, 2014 ), endothelial cells (Navaratna et al, 2011 ; Prigent-Tessier et al, 2013 ) or both (Monnier et al, 2017a ). Using cell culture, activation of endothelial TrkB receptors was reported to induce myotubes formation (angiogenesis) (Kim et al, 2004 ), while activation of neuronal receptors was reported to increase the number of synaptic connections (Park and Poo, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that endothelial BDNF expression in arterioles and cerebral capillaries might differ. However, the difference if present is expected to be minor since endothelial BDNF staining/levels did not singificantly differ amoung F20, F53, and F110 fractions (Monnier et al, 2017a ). According to such a paracrine action, BDNF secreted by cerebral capillaries into the cerebral interstitial fluid might be recognized by and activate neuronal TrkB receptors thereby increasing synapses strength and cognitive abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that patients with substance use disorder usually exhibit decreased inhibitory response on the Stroop test (Hillman & Drobes, 2012), and that an acute session of aerobic exercise improves the performance on inhibitory control associated with greater activity on electrophysiological records of the PFC (Wang, Zhou, Zhao, Wu, & Chang, 2016). Interestingly, exercise has been related to increased levels of brain-derived neurotrophic factor, which plays an important role on several molecular changes that might enhance cognitive functions (Monnier et al, 2017). In addition, exercise has also been shown to improve neurogenesis (van Praag, 2008).Taken together, these PFC and cognitive improvements are extremely important to this individual, because it might lead to greater impulsivity control and abstinence maintenance, thereby decreasing the negative effects on cognitive functions induced by chronic drug intake.…”
Section: Discussionmentioning
confidence: 99%